INTERAKSI SOSIAL ONLINE DAN KECEMASAN SOSIAL SEBAGAI PREDIKTOR KECANDUAN INTERNET PADA REMAJA - Putra Hidayat (Jurnal Ilmiah Psyche, 2020)
This study aims to examine the effect of online social interaction and social anxiety on internet addiction in adolescents. Employing an ex-post facto design, this research was conducted in the regency of Purbalingga involving 366 teenagers as sample which was determined using a multistage random sampling techniques. Data were collected through questionnaires consisting of internet addiction questionnaires, online social interaction questionnaires, and social anxiety questionnaires. These instruments were validation through content validity and reliability based on Cronbach’s Alpha coefficient. The data where then analysed by means of a multiple regression analysis.The results showed that there was a significant effect of online social interaction and social anxiety on internet addiction in adolescents (p=0,000). Therefore, it can be concluded that there is a effect between online social interaction and social anxiety towards the adolescents internet addiction. Online social interaction and social anxiety can be strong predictors of internet addiction among adolescents.